GENDER ISSUES IN PHYSICAL EDUCATION CLASSES, TEACHER EDUCATION AND CRITICAL-HISTORICAL PEDAGOGY - Siqueira, Jaqueline Cristina Freire; Silva, Luciene Ferreira da [UNESP] (Unesp-faculdade Ciencias & Letras, 2023)
Neoliberal public policies are harmful to education. Currently, the National Base for Teacher Education (BRASIL, 2019) and the National Common Curricular Base (BRASIL, 2017) are aligned in an attempt to make the education of students in public schools even more precarious. Both in basic education and higher level, an instrumental, superficial and quick technical teacher training aims at meeting the market needs. The purpose of this essay is to understand gender issues in physical education classes, by analyzing the speeches of teachers from a municipal school system in the State of Sao Paulo at the current moment, having historical-critical pedagogy as a reference and counterpoint. From common sense to philosophical awareness to overcome aggressive and destructive neoliberal policies for Brazilian society.
Keywords: Education; Physical Education; Gender; Teacher Education; Critical Historical Pedagogy